Faixas de temperatura ambiente para codornas de corte dos 22 aos 42 dias - Lima, Cristina Aparecida Barbosa de (2014)
The objective of this study was to determine the optimum temperature range for European quail through behavioral , physiological , blood and performance indicators 480 European quail ( Coturnix coturnix coturnix ) were used in the period 22-42 days of age. The experimental design was completely randomized with six treatments (temperatures - 15, 19, 23, 27, 31 and 35ºC) and eight replicates , totaling 48 experimental units . Ingestive pattern , location , position and interaction: were observed Physiological variables such as: sewage and surface temperature. After the experimental period, two birds from each experimental unit , collected blood samples for assessment of the heterophil / lymphocyte were slaughtered . We evaluated body weight ( g ) , weight gain ( g / d ) , feed intake ( g / d ) and feed conversion ( g / g ) , and even absolute weight ( g ) and yield ( % ) of whole carcasses (without feet and head ) , prime cuts , chest and legs ( thigh and drumstick ). Data were statistically analyzed by analysis of variance and regression . Quails kept at temperatures of 19-23 ° C had higher frequency of feeding, water intake was greater as the temperature increased , the quail remained alone in the high temperature ( 35 ° C) and lumped in cold temperature ( 15°C), the location and position of the quails were influenced by environmental temperature . Linear increase occurred in the physiological variables, which rose as the environmental temperature increased ( 35 ° C ) except peito. Was found an increase in the percentage of heterophils and reduction of lymphocytes when quails were maintained at elevated temperature. The end weight, weight gain and feed consumption of quail maintained at temperatures of 31-35°C were lower than those reared in warmer temperatures . The range of 19 to 27°C of temperature environmental is recommended as being good for quail from 22 to 42 days old .